Audit Kepatuhan Sistem Informasi Akuntansi Pembelian Barang Secara Kredit Melalui Deteksi Pengendalian Studi Kasus Toko Elektronik - Novia Oktaviani Febrilia; Meilita Rizkynanda; Tri Ratnawati (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2023)
Every business has a buying process, be it services, buying and selling, manufacturing or industry, including the purchasing system that occurs at the New Palapa Rungkut Surabaya Store. This purchase transaction is divided into two, namely cash and credit purchases. In this article, we will present a credit purchase accounting information system at the New Pala Elektronik Store in Rungkut. The research method that we use is descriptive qualitative which aims to find out how the accounting information system for credit purchases at electronic stores. The results of this study are, there are still some parts that are lacking, namely the receiving of goods and IT. So we suggest adding this section to make it easier for the internal control section in the credit purchasing process.